GH treatment in pediatric Down syndrome: a systematic review and mini meta-analysis - Shaki, David; Hershkovitz, Eli; Tamam, Shai; Bollotin, Arkadi; David, Odeya; Yalovitsky, Guy; Loewenthal, Neta; Carmon, Lior; Walker, Dganit; Nowak, Raphael; Haim, Alon (Frontiers in Endocrinology, 2023)
Objective: To analyze and determine the safety and efficacy of growth hormone (GH) treatment in Down Syndrome (DS) pediatric patients and to weigh ethical aspects involved. Design: Systematic review and mini meta-analysis of the literature. Methods: A search was performed in PubMed, Embase, Scopus, and PsycINFO through August 2022. Eligible studies included those who answered at least one of the following two questions: 1- What is the effect of growth hormone treatment in children with Down syndrome. 2- What are the ethical arguments in favor and against growth hormone treatment for children with Down syndrome. Multiple reviewers independently screened each article for eligibility. Results: In total sixteen reports detailed medical effects of GH treatment in pediatric DS patients and eight studies dealt with ethical aspects of GH treatment. Treatment with GH resulted in significantly higher growth velocity in patients with DS. The ethical complexity is great, but does not present insurmountable difficulties to the therapeutic option. Conclusions: As GH treatment is safe and effective for short-term height growth, GH therapy should be considered in long-term treatment of DS children.